2012
DOI: 10.1186/1743-0003-9-21
|View full text |Cite
|
Sign up to set email alerts
|

A review of wearable sensors and systems with application in rehabilitation

Abstract: The aim of this review paper is to summarize recent developments in the field of wearable sensors and systems that are relevant to the field of rehabilitation. The growing body of work focused on the application of wearable technology to monitor older adults and subjects with chronic conditions in the home and community settings justifies the emphasis of this review paper on summarizing clinical applications of wearable technology currently undergoing assessment rather than describing the development of new we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1,030
0
21

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,822 publications
(1,052 citation statements)
references
References 99 publications
1
1,030
0
21
Order By: Relevance
“…The use of body-worn sensors for in-home rehabilitation is an emerging healthcare application domain (Patel et al, 2012). These virtual reality applications typically consist of body-worn sensors, interactive software, and real-time representations of the patient.…”
Section: Biomechanical Rehabilitationmentioning
confidence: 99%
“…The use of body-worn sensors for in-home rehabilitation is an emerging healthcare application domain (Patel et al, 2012). These virtual reality applications typically consist of body-worn sensors, interactive software, and real-time representations of the patient.…”
Section: Biomechanical Rehabilitationmentioning
confidence: 99%
“…A 2012 review of wearable and ambient sensing systems for health and rehabilitation highlighted the potential of objective monitoring for home-based rehabilitation interventions [9]. In addressing dementia, the authors observed that an "important factor in this patient population is that the monitoring system must be totally unobtrusive and, if possible, collect information in a transparent way without patient intervention".…”
Section: Introductionmentioning
confidence: 99%
“…For instance, gait analysis has been used to assess musculoskeletal complications, disease due to aging, cardiopathies, and neurological conditions such as stroke, Parkinson's disease, and multiple sclerosis [1]- [7]. Gait analysis can reflect the quality of life of patients and the effect of treatment and rehabilitation programs [5], [7]- [10].…”
Section: Introductionmentioning
confidence: 99%